On the line ratio diagnostics for NeV, MgV, SiVII and Mg VII solar ions - Dwivedi B.N.; Mohan A.; Raju P.K. (My University, 2025)
We present NeV/MgV and MgVII/SiVII theoretical line intensity ratios as a function of electron density and temperature for physical conditions within the solar chromosphere-corona transition region. The electron pressure within the emission regions has been assumed to be a constant parameter. These line intensity ratios in addition could be useful for estimating relative element abundances Ne/Mg and Mg/Si. Line intensities of these ions have been computed using a model solar atmosphere and these have been compared with the available observed values for the quiet -Sun conditions. The analysis suggests the need for observations at higher spectral resolution. The successful launch of the SOHO satellite recently should provide such spectra. © 1997 COSPAR. Published by Elsevier Science Ltd.